Better location shooting : techniques for video production. - Martingell, Paul, ....- (Burlington, MA : Focal, 2008)
Key Features - Learn the basics of shooting properly on location - no matter what equipment you are using - Includes the latest camera information - Covers the gamut of types of location filming - Realistic/practical information Description Location filming is growing in popularity with the abundance of affordable cameras. You don't need a studio, a broadcast truck, or even extensive knowledge of how to use a 16mm film camera--all you need is a digital camera, and you can take your job on the road and shoot wherever action is happening! This book will give you the knowledge and confidence you need to take your on-location shooting skills to the next level. Better Location Filming is packed with the things you will need to know to have great results while shooting your documentary, interview, sporting event, fashion or glamour event, or current affairs/news show. Beyond introductory techniques, the author will tell you how to plan, troubleshoot, handle legal requirements and issues, and of course - he'll teach you all about location filming equipment. Practical and filled with hands-on pointers, this book is perfect for working and aspiring film & video professionals seeking a leg up in their careers. As a bonus, advanced tips are included for novices who are ready to take shooting techniques to the next level.
Keywords: Audiovisuele media -- Producties; Filmtechnieken -- Locaties